The impact of organizational commitment on turnover intention of substitute teachers in public primary schools: Taking psychological capital as a mediator - Zhu, Kexuan; Wang, Xinyi; Jiang, Man (Frontiers in Psychology, 2022)
This research aimed to explore the impact of organizational commitment on turnover intention of substitute teachers in public primary schools in Xuzhou, and applied psychological capital as a mediator variable to establish a research model. A questionnaire was conducted with 400 substitute teachers using convenience sampling. The results show that organizational commitment has a negative yet significant effect on turnover intention. It also shows positive impact on psychological capital. Furthermore, psychological capital is shown to negatively impact turnover intention, while having a mediating effect between organizational commitment and turnover intention.